Genome-wide identification of the GT7 and GH16 genes and their correlations with agar metabolism in the agarophyte Gracilariopsis lemaneiformis - Chen, Qionglin; Ying, Xiao; Hu, Chaoyang; Liu, Shixia; Xu, Nianjun; Sun, Xue (Frontiers in Marine Science, 2023)
The economically important seaweed Gracilariopsis lemaneiformis (Gp. lemaneiformis) is the main resource for agar production and abalone bait. Few studies have focused on the functions of glycosyltransferases (GTs) and glycoside hydrolases (GHs) involved in saccharometabolism, including that of agar. To investigate the possible functions of glycosyltransferase family 7 (GT7) and glycoside hydrolase family 16 (GH16) members in agar metabolism, analyses of these gene families were conducted using bioinformatics-based and physiological methods. In total, five GlGT7 genes and four GlGH16 genes from the Gp. lemaneiformis genome were identified and analyzed. These GT7 and GH16 members are absent in higher plants, and the majority of GlGT7s and GlGH16s have no introns. Catalytic pocket residue analysis revealed that GlGT7s may function as β-1,4-galactosyltransferases and that GlGH16s play roles as agarases. Promoter prediction and qRT-PCR experiments verified that these genes can be regulated by light and phytohormones. GlGT7s were predicted to interact with carbohydrate sulfotransferases (STs), whereas yeast two-hybrid (Y2H) assays revealed no interactions between these proteins. Under heat stress, no significant difference was found in agar content; however, the expression of GlGT7s fluctuated and that of GlGH16 increased. Low nitrogen stress significantly increased the agar content, and the expression of GlGT7s increased, whereas that of GlGH16s decreased. In three cultivars of Gp. lemaneiformis, the expression of GlGT7 genes in cultivars 981 and Lulong No. 1 was upregulated relative to that in the wild type, whereas GlGH16 expression levels were significantly decreased. Fluorescence microscopy further showed that β-1,4-galactose accumulation was consistent with increases in agar content and GlGT7 expression. Pearson correlation analysis confirmed that the expression levels of GlGT7s and GlGH16s were positively and negatively correlated with agar accumulation, respectively. Taken together, these results demonstrated that GlGT7 and GlGH16 are intimately correlated with agar metabolism; in particular, GlGT7-2, GlGT7-5, and GlGH16-4 could act as molecular markers to indicate agar yield. This study will provide a valuable basis for breeding new cultivars with high agar content.